Staphylococcus aureus N-terminus formylated δ-toxin tends to form amyloid fibrils, while the deformylated δ-toxin tends to form functional oligomer complexes. Issue 1 (1st January 2021) - Zhou, Xinyu; Zheng, Yuling; Lv, Qingyu; Kong, Decong; Ji, Bin; Han, Xuelian; Zhou, Dongsheng; Sun, Zeyu; Zhu, Li; Liu, Peng; Jiang, Hua; Jiang, Yongqiang
ABSTRACT: The community-associated Methicillin-resistant Staphylococcus aureus strain (CA-MRSA) is highly virulent and has become a major focus of public health professionals. Phenol-soluble modulins (PSM) are key factors in its increased virulence. δ-Toxin belongs to PSM family and has copious secretion in many S. aureus strains. In addition, δ-toxin exists in the S. aureus culture supernatant as both N-terminus formylated δ-toxin (fδ-toxin) and deformylated δ-toxin (dfδ-toxin) groups. Although δ-toxin has been studied for more than 70 years, its functions remain unclear. We isolated and purified PSMs from the supernatant of S. aureus MW2, and found fibrils and oligomers aggregates by Size Exclusion Chromatography. After analyzing PSM aggregates and using peptide simulations, we found that the difference in the monomer structure of fδ-toxin and dfδ-toxin might ultimately lead to differences in the aggregation ability: fδ-toxin and dfδ-toxin tend to form fibrils and oligomers respectively. Of note, we found that fδ-toxin fibrils enhanced the stability of biofilms, while dfδ-toxin oligomers promoted their dispersal. Additionally, oligomeric dfδ-toxin combined with PSMα to form a complex with enhanced functionality. Due to the different aggregation capabilities and functions of fδ-toxin and dfδ-toxin, we speculate that they may be involved in the regulation of physiological activities of S. aureus . Moreover, the dfδ-toxin oligomer not only provides a new form of complex in the study of PSMα, but also has significance as a reference in oligomer research pertaining to some human amyloid diseases.